SIKLUS AIR DALAM QS. AR-RA’D AYAT 17 MENURUT AL JAWAHIR FI TAFSIR AL-QUR'AN AL-KAREEM - Nietarahmani, Putri Fathiya; Muhammad, Hafid Nur; Setiawan, Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
The role of water is very important for the sustainability of life. Given that water is the primary need of all creatures on earth, including humans, including animals, plants and so on. That way the rotation of the water cycle that continues to run makes water will not run out and is always maintained. By understanding the vital role of water for the sustainability of life on earth, did you know that this water cycle is mentioned in the Qur'an with various terms. In scientific terms this is referred to as hydrology. In this research, the author seeks to explore and understand how the interpretation of QS. Ar-Ra'd verse 17 and how the cycle occurs in the Qur'an. The data obtained in this research comes from library research. This research reveals how the interpretation of QS. Ar-Ra'd verse 17 which is reviewed from the analysis of the book Tafsir Al Jawahir fi Tafsir Al-Qur'an Al-Kareem which is the work of Sheikh Thantawi Jauhari. The resulting research is that the Qur'an explains about water with various terms starting with how the process of lightning, lightning and rain occurs so that it is continuous with the water cycle that occurs on earth. Sheikh Thantawi Jauhari interpreted this verse with various parables, so that what is useless will be blown away then what is useful will continue to exist on earth like water.